Exploring concentration, surface area and surface chemistry effects of colloidal aggregates on fat crystal networks - Chauhan, R; Dullens, R; Velikov, K; Aarts, D (Royal Society of Chemistry, 2017)
We study the effects of concentration, surface area and surface chemistry of fractal fumed silica aggregates on a model fat-structured food system. We use oscillatory stress sweep rheology to determine the storage modulus, the length of the linear viscoelastic region and the rate of network breakdown after the linear region. Differential scanning calorimetry shows that silica is not acting as a seed for nucleation and that the melting profiles for samples with silica are not significantly different. We interpret these results in terms of hydrogen bonding between the silica aggregates and its role in strengthening the fat crystal networks.